2013
DOI: 10.1007/s00429-013-0651-2
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein in the olfactory system in Parkinson’s disease: role of neural connections on spreading pathology

Abstract: Parkinson's disease (PD) is a neurodegenerative disease characterized by bradykinesia, rigidity, resting tremor, and postural instability. Neuropathologically, intracellular aggregates of α-synuclein in Lewy bodies and Lewy neurites appear in particular brain areas according to a sequence of stages. Clinical diagnosis is usually established when motor symptoms are evident (corresponding to Braak stage III or later), years or even decades after onset of the disease. Research at early stages is therefore essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 142 publications
1
66
0
4
Order By: Relevance
“…α-Synuclein may be the target of this unknown agent causing protein misfolding and subsequent spread of α-synuclein via connecting cells. Hence, olfactory deficits are an early non-motor feature of PD and the pathology could potentially spread via the olfactory bulb and vagal system to the substantia nigra [36]. Further spread into cortical and limbic areas could then occur with subsequent propagation of the pathology among cortical regions …”
Section: Discussionmentioning
confidence: 99%
“…α-Synuclein may be the target of this unknown agent causing protein misfolding and subsequent spread of α-synuclein via connecting cells. Hence, olfactory deficits are an early non-motor feature of PD and the pathology could potentially spread via the olfactory bulb and vagal system to the substantia nigra [36]. Further spread into cortical and limbic areas could then occur with subsequent propagation of the pathology among cortical regions …”
Section: Discussionmentioning
confidence: 99%
“…The olfactory cortex also receives inputs from cholinergic and monoaminergic neurons in the basal forebrain, hypothalamus, and brainstem [27] Olfactory information is transmitted from the primary olfactory cortex (POC) to other cortical and subcortical areas, all having reciprocal connections with the POC to integrate olfactory information with other sensory modalities [3]. Hence, the olfactory system displays a complex system of centripetal, centrifugal, commissural, and associated connections, as well as reciprocal direct and indirect connections with other essential brain areas [4,24]. …”
Section: The Olfactory Systemmentioning
confidence: 99%
“…Like the OE, a number of OB cells undergo periodic replacement as neuroblasts from the subgranular zone (dentate gyrus) and migrate via the rostral migratory stream into the OB, resulting in plasticity within the glomerular region of the OB throughout life [23]. The mitral and tufted cell axons project to central olfactory structures, including the anterior olfactory nucleus (AON), a nodal point in the olfactory system, the olfactory tubercle that is reciprocally connected with the substantia nigra [24], the pyriform cortex (area 51), the largest cortical olfactory area and crucial in odour quality coding, the rostral entorhinal cortex, and the corticobasal nuclei of the amygdala. Since the afferent projections of the olfactory system to the cortex bypass the thalamus, the OB has been suggested to constitute the ‘olfactory thalamus' [25].…”
Section: The Olfactory Systemmentioning
confidence: 99%
“…Olfactory tests, including ethnically specific odors, were recommended by the European Federation of Neurological Societies and the Movement Disorder Society as screening tests for pre-motor PD [10]. Moreover, the fact that α-synuclein deposits are present in the olfactory bulb and anterior olfactory nucleus at Braak stage I explains its high sensitivity in early PD [11]. A study that correlated diffusion tensor imaging (DTI) with olfactory deficit in early PD patients demonstrated that the Fractional anisotropy (FA) values of White Matter (WM) were significantly reduced in the early PD group versus healthy controls [12].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the utilization of SS-16 was compared among different countries with China included. The results suggested that the scores of several items called “component1” were significantly different across PD patients from different country groups because of culture, smell familiarity and environmental variations [11, 16]. Our previous study used the adapted SS-16 translational version evaluation (mentioned in the methods) in Chinese patients, resulting in a sensitivity of 86 % and the specificity of 81 % in discriminating PD patients from healthy controls.…”
Section: Discussionmentioning
confidence: 99%